Comparative Analysis of Tsukamoto and Sugeno Fuzzy Methods For Procurement Optimization - Fahrul Agus; Hairunnisa Hairunnisa; Septya Maharani (International Journal of Computing and Informatics (IJCANDI), 2016)
This paper aims to conduct a comparative analysis of appropriate methods between Tsukamoto and Sugeno fuzzy method in solving optimization problems approximate amount of procurement. The analysis is done by comparing the average value of the relative error in the calculation results forecasts procurement of data procurement of goods belonging to a company. The results of the analysis is implemented in an application program and obtained value of the average relative error Tsukamoto method by 39.67% and amounted to 50.39 % of Sugeno method. Based on these results, Tsukamoto method is more appropriate and recommended to solve optimization of the approximate number of procurement.